Outlier Detection in 3D Coordinate Transformation with Fuzzy Logic - Şişman, Yasemin; Dilaver, A.; Bektaş, S. (My University, 2012)
Coordinate measurements inevitably contain outliers that affect the results of transformation. Conventional methods based on the leasts squared method determine the outliers by minimizing the selected objective function. Fuzzy Logic can be used to analyze the outliers. In this study, several outlier detection methods are described and applied to a real case consisting of a triangulation network. Results show that for outlier detection methods are not as efficient as Fuzzy provides a non-iterative solution in contrast to conventional methods.
Keywords: Conventional Methods; Coordinate Transformation; Fuzzy Logic; Outliers Detection